Explorer travellers and adventure tourism - Laing, Jennifer; Frost, Warwick (Tourism and cultural change, 2014)
This book examines the nexus between exploring and tourism and argues that exploration travel-based heavily on explorer narratives and the promises of personal challenges and change is a major trend in future tourism.